2019
DOI: 10.1155/2019/8194804
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology and Microbiome Dissection of Shen Ling Bai Zhu San Reveal Multiscale Treatment Strategy for IBD

Abstract: Generally, inflammatory bowel disease (IBD) can be caused by psychology, genes, environment, and gut microbiota. Therefore, IBD therapy should be improved to utilize multiple strategies. Shen Ling Bai Zhu San (SLBZS) adheres to the aim of combating complex diseases from an integrative and holistic perspective, which is effective for IBD therapy. Herein, a systems pharmacology and microbiota approach was developed for these molecular mechanisms exemplified by SLBZS. First, by systematic absorption-distribution-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 87 publications
0
25
0
Order By: Relevance
“…Thus, it is important to find alternative drugs for the alleviation of pneumoniainduced deaths. SLBZS is a well-known TCM formula used in China for the treatment of gastrointestinal disorders such as diarrhea, ulcerative colitis, and inflammatory bowel disease (IBD) [13,25,26]. This study showed that SLBZS or cefixime treatment decreased bacterial load in BALF, reduced wet/dry weight ratio, inhibited MPO activity and reduced neutrophils count in BALF, and ameliorated lung injury in Spn-induced pneumonia, suggesting that these treatments ameliorates lung injury in Spn-induced pneumonia mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to find alternative drugs for the alleviation of pneumoniainduced deaths. SLBZS is a well-known TCM formula used in China for the treatment of gastrointestinal disorders such as diarrhea, ulcerative colitis, and inflammatory bowel disease (IBD) [13,25,26]. This study showed that SLBZS or cefixime treatment decreased bacterial load in BALF, reduced wet/dry weight ratio, inhibited MPO activity and reduced neutrophils count in BALF, and ameliorated lung injury in Spn-induced pneumonia, suggesting that these treatments ameliorates lung injury in Spn-induced pneumonia mice.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, researchers apply the systems pharmacology method to explore the pharmacological mechanisms of SLBZS, and found the changes of IL-1β, IL-10, and TNF-α after SLBZS treatment (0.6 g/mL). IL-1β and TNF-α participated in the MAPK and NF-κB pathways, and the two pathways share crosstalk in DSS-induced UC rats [133].…”
Section: Tonifying Qi and Activating Blood Categorymentioning
confidence: 96%
“…All networks were visualized using Cytoscape software (version 3.7.1) [88]. e target location network was generated based on the analysis of gene expression data of various hematopoietic tissues and organs obtained from e Human Protein Atlas [89] and BioGPS databases [90]; this network was generated by linking the target to the corresponding tissues and organs where it was analyzed to be specifically expressed using previously described procedures [91][92][93][94][95][96][97][98]. e protein-protein interaction (PPI) network was constructed using the STRING database (version 11.0) [99] and interactions with highest confidence scores (≥0.9) were selected for further analysis.…”
Section: Construction Of Smt-associated Networkmentioning
confidence: 99%
“…To understand the therapeutic effects of SMT at the tissue-and organ-level, we generated a target location network based on the gene expression data for individual myelosuppression-associated SMT targets across various tissues and organs, which were identified from e Human Protein Atlas [88] and BioGPS databases [90] and analyzed as previously described [91][92][93][94][95][96][97][98] (Figure 5; see Materials and Methods). Consequently, we found that the targets were expressed in various hematopoietic tissues and organs [129,130], including the liver (degree = 144), bone marrow (degree = 137), spleen (degree = 116), lymph nodes (degree = 113), and blood (degree = 100) ( Figure 5), which suggests the systematic mechanism of action responsible for the pharmacological effects of SMT.…”
Section: Network-based Analysis Of the Pharmacological Mechanisms Of mentioning
confidence: 99%